Analisi di minimizzazione dei costi del trattamento della leucemia cronica con fludarabina fosfato (Fludara®) e.v. e p.o.: metodologia e risultati di un’indagine empirica - Lazzaro, Carlo (Farmeconomia. Health economics and therapeutic pathways, 2004)
The aim of the paper is to compare healthcare-related costs of a 5-day course with fludarabine phosphate i.v. vs a 5-day course with oral fludarabine phosphate in Italian patients with chronic leukemia. A cost-minimization analysis was performed from both Italian National Healthcare Service (INHS) and hospital perspectives. Healthcare-related costs were collected from 2 out of a sample of 28 Ematology wards and included those of drug acquisition, drug preparation, drug administration, reception and discharge of patient before and after drug administration; hospital overheads were calculated as a percentage of the total healthcare-related costs. The reimbursement schemes for acquisition and administration of fludarabine phosphate i.v. were gathered from the whole sample of 28 Ematology wards taken into account. Costs were expressed in euros 2004. When compared to fludarabine phosphate i.v., oral fludarabine phosphate allowed savings ranging from 223,47 euros (hospital perspective) to 477,05 euros (INHS perspective) per patient. As far as hospital perspective was concerned, savings associated with oral fludarabine phosphate were due to hospital overheads (115.1%), drug preparation (19.6%), drug administration (17.3%), reception and discharge of patient before and after drug administration (2.9%), whereas costs for drug acquisition was higher for oral formulation (-54.8%). When INHS perspective was taken into account, 3 out of 28 Ematology wards (11%) were reimbursed on a drug-plus-outpatient-drug-administration-basis, whereas 25 out of 28 Ematology wards (89%) were reimbursed on a day-hospital-stay-basis. Savings associated with oral fludarabine phosphate were due to day-hospital stay (253.4%), outpatient drug administration (1.1%), whereas cost for drug acquisition were higher for oral formulation (-154.5%). Sensitivity analysis confirmed the robustness of basecase results. Savings associated with oral fludarabine phosphate may be of relevant interest for INHS policies aimed at reducing public expenditure for drugs in Italy.